TNFR2 blockade alone or in combination with PD-1 blockade shows therapeutic efficacy in murine cancer models. Issue 6 (24th May 2020) - Case, Katherine; Tran, Lisa; Yang, Michael; Zheng, Hui; Kuhtreiber, Willem M.; Faustman, Denise L.
Abstract: Immune checkpoint inhibitors are profoundly transforming cancer therapy, but response rates vary widely. The efficacy of checkpoint inhibitors, such as anti-programmed death receptor-1 (anti-PD-1), might be increased by combination therapies. TNFR2 has emerged as a new target due to its massive expression on highly immunosuppressive regulatory T cells (Tregs) in the microenvironment and on certain tumor cells. In murine colon cancer models CT26 and MC38, we evaluated the efficacy of a new anti-TNFR2 antibody alone or in combination with anti-PD-1 therapy. Tumor-bearing mice were treated with placebo, anti-PD-1 alone, anti-TNFR2 alone, or combination anti-PD-1 and anti-TNFR2. We found that combination therapy had the greatest efficacy by complete tumor regression and elimination (cure) in 65–70% of animals. The next most effective therapy was anti-TNFR2 alone (20–50% cured), whereas the least effective was anti-PD-1 alone (10–25% cured). The mode of action, according to in vivo and in vitro methods including FACS analysis, was by killing immunosuppressive Tregs in the tumor microenvironment and increasing the ratio of CD8+ T effectors (Teffs) to Tregs. We also found that sequence of antibody delivery altered outcome. The two most effective sequences were simultaneous delivery (70% cured) followed by anti-TNFR2 preceding anti-PD-1 (40% cured), and the least effective was by anti-PD-1 preceding anti-TNFR2 (10% cured). We conclude that anti-PD-1 is best enhanced by simultaneous administration with anti-TNFR2, and anti-TNFR2 alone may be potentially useful strategy for those do not respond to, or cannot tolerate, anti-PD-1 or other checkpoint inhibitors.